PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS INKUIRI TERBIMBING DALAM MEREDUKSI KESALAHAN PESERTA DIDIK MENYELESAIKAN SOAL PEMBELAHAN SEL - Yolan Dunggio; Ani Hasan; Frida Maryati Yusuf (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This development research produce a Lesson Plan (RPP) and Worksheet Students (LKPD) based on Guided Inquiry on the material Cell Division for students Class XII SMA Limboto Barat. Development aims to find out the quality, feasibility of RPP and LKPD based on aspects of validity, practicality, and effectiveness. Product development follow the steps of the R&D development model, namely the research step and the development step. The product was assessed by three validators with an assessment instrument. The results of development research show that the validity aspect of RPP obtains very valid criteria with an average score of 43.67 and LKPD obtains a very valid criterion with an average score of 198.67. For practicality aspects, the results of the responses of students get a percentage of 90.91% with very good criteria (strongly agree and agree), while the teacher's response gets a percentage of 100% with good criteria (agree and strongly agree). Furthermore, the observation of the implementation of the RPP obtained an average score of 82.06 while the activities of the students scored an average score of 78.13. This shows that the average scores of RPP and LKPD are included in very practical criteria. Furthermore, for the aspect of effectiveness based on the percentage of classical learning completeness. the pre-test obtained a percentage of 0.81% with the criteria not good, while the post-test obtained 81% with good criteria, and classically the results of the LKPD task gained 88.89%, with very good criteria. Keywords: RPP, LKPD, development, guided inquiry, cell devision.